Molecular tools for selective recovery and detection of lignin-derived molecules - Milla Salmela; Hanna Sanmark; Elena Efimova; Alexander Efimov; Vesa P. Hytönen; Urpo Lamminmäki; Suvi Santala; Ville Santala (ROYAL SOC CHEMISTRY, 2022)
The pulp and paper industry together with lignocellulosic biofuel production provides plentiful streams of lignin and lignin-derived molecules (LDMs) that currently remain underutilized. The heterogeneity and complexity of lignin along with the lack of convenient tools significantly hamper its utilization. Selective separation of these LDMs from streams using specific tools would allow the recovery of aromatic compounds, as well as facilitate biological processes aiming at lignin valorization. To this end, here we report the isolation and characterization of single-chain variable fragment (scFv) antibodies against ferulate, coumarate, and caffeate, which are the molecular representatives of LDMs. Binders for the target LDMs were enriched by interrogating a synthetic scFv library with the phage display technique. As a result, scFv binders specific against each of the target molecules were obtained with affinities in the micromolar range. The selectivity of scFvs towards specific LDMs was proved by recovering caffeate from simulated LDM solution, Kraft lignin, and rice straw hydrolysate samples. Further proof of concept studies with model compounds demonstrated the applicability of antibody-based binders as a detection tool for monitoring microbial LDM conversion. Overall, this study demonstrates the potential of scFv binders as a specific toolset for lignin compound recovery and analysis.